2020
DOI: 10.13031/aea.13488
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable-based Oil as UTTO Fluid for Agricultural Tractors Application

Abstract: HighlightsLubricants are commonly used in agricultural activities involving machines.To reduce lubricants impact on the environment, a process has been started for replacing them with products obtained from vegetable oils.Tests have been carried out to explore the possibility of introducing vegetable-based UTTO in tractors.Results encourage to deepen the behavior of vegetable-based oils and develop specific test bench and methods.Abstract. To reduce the impact of mineral and synthesis lubricants on the environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Before the introduction of bio-based fluids in real-world conditions, these encouraging results have to be confirmed in tests representative of real working conditions, where their performance must be at least equivalent to those of the conventional fluids they have to replace. In this respect, a first series of tests on a tractor in service showed good performance of a bio-based UTTO fluid compared to a conventional one [28]. However, in spite of its relative short duration, the test also evidenced the initial process of fluid degradation.…”
Section: Introductionmentioning
confidence: 93%
“…Before the introduction of bio-based fluids in real-world conditions, these encouraging results have to be confirmed in tests representative of real working conditions, where their performance must be at least equivalent to those of the conventional fluids they have to replace. In this respect, a first series of tests on a tractor in service showed good performance of a bio-based UTTO fluid compared to a conventional one [28]. However, in spite of its relative short duration, the test also evidenced the initial process of fluid degradation.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, it has been demonstrated that vegetable oils have high flash points, a high viscosity index, and low volatility [9]. The biggest drawback of using vegetable oil is its low thermal and oxidative stability [10]. The use of modifiers such as friction modifiers (FMs) has been shown to greatly reduce friction.…”
Section: Preparation For Bio Lubricantsmentioning
confidence: 99%
“…The reported data of work and energy have been calculated basing on the above-mentioned test interval of 150 h as a reference. Oil volume in the multiplier dm 3 2.6 Oil temperature 3 • C 60 Oil temperature 4 • C ≈87 Flowrate 5 dm 3 min −1 0.2 Electric engine speed min −1 660 Dynamometric brake shaft speed min −1 1670 Torque at dynamometric brake 6 daNm 10.4 Mechanical power 6 kW 18.2 1 In the reservoir/before high-pressure pump. 2 After the lamination at 40 MPa.…”
Section: Test Conditionsmentioning
confidence: 99%
“…At first, the suitability of biobased lubricants is usually assessed in proper work cycles based on special test benches, by monitoring the fluid properties through periodic samplings and laboratory analyses, capable of providing accurate information on the oil status [4,5]. The next evaluation step is based on the use of real machines (e.g., tractors) employed in normal work (e.g., farming operations), always monitoring the fluid status by sample analysis [6]. Such a method often requires the intervention of specialized (often external) laboratories and its limits consist of the costs, the time for analyses, and the time interval between samplings during which the fluid-machine system is exposed to undetectable variations or damage.…”
Section: Introductionmentioning
confidence: 99%